2017
DOI: 10.1371/journal.ppat.1006168
|View full text |Cite
|
Sign up to set email alerts
|

Identification of several high-risk HPV inhibitors and drug targets with a novel high-throughput screening assay

Abstract: Human papillomaviruses (HPVs) are oncogenic viruses that cause numerous different cancers as well as benign lesions in the epithelia. To date, there is no effective cure for an ongoing HPV infection. Here, we describe the generation process of a platform for the development of anti-HPV drugs. This system consists of engineered full-length HPV genomes that express reporter genes for evaluation of the viral copy number in all three HPV replication stages. We demonstrate the usefulness of this system by conductin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 81 publications
1
21
0
Order By: Relevance
“…The DpnI-resistant replication signal strengths were quantified and expressed relative to the vehicle-only control (DMSO), and the inhibition curves and IC50 values for each compound are provided in Fig 4. The results indicate that all five compounds inhibited the replication intensity of the MfPV8 genomes in a concentration-dependent manner, with IC50 values ranging from 5.7 to 58.9 μM (Fig 4), which are very similar to what is seen for HPV18, for example [32]. Thus, MfPV genome replication in U2OS cells can potentially be used for screening or validation of anti-HPV drugs.…”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…The DpnI-resistant replication signal strengths were quantified and expressed relative to the vehicle-only control (DMSO), and the inhibition curves and IC50 values for each compound are provided in Fig 4. The results indicate that all five compounds inhibited the replication intensity of the MfPV8 genomes in a concentration-dependent manner, with IC50 values ranging from 5.7 to 58.9 μM (Fig 4), which are very similar to what is seen for HPV18, for example [32]. Thus, MfPV genome replication in U2OS cells can potentially be used for screening or validation of anti-HPV drugs.…”
Section: Resultssupporting
confidence: 60%
“…We demonstrated that the human osteosarcoma cell line U2OS supports the genome replication of alpha and beta HPVs and is suitable for studying HPV genome replication and transcription [2632,42]. To identify whether the same cell line also supports the replication of the MfPV genomes, a transient replication assay mimicking the phase of the establishment of the viral infection was performed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations